A New Lighthouse on the Horizon: The Emergence of ASEAN-China Comprehensive Strategic Partnership (Global Focus, 2023)
Recently, China has made a comprehensive strategic partnership (CSP) with ASEAN that would open up more opportunities for the two parties. However, some view it as another success on China’s part as it now has gained influence over ASEAN. But such a view that downplays ASEAN into a mere instrument for China’s plan in the region would not provide a proper view. Through the use of qualitative research methods over data gathered through the internet and documents, the article seeks to shed light over the forthcoming points. First, the article lays out the things that the CSP brings both for ASEAN-China relations and ASEAN’s standing in the Indo-Pacific. Here, the partnership paves the way for stronger ties between ASEAN and China, not to mention the impact it has towards ASEAN’s growing centrality. The article then proceeds with the challenges that may arise following the emergence of the partnership. On this matter, the inconsistent cohesion within ASEAN along with the ongoing competition for influence in the region can be viewed as some of the challenges. After that, a discussion over the many opportunities for enhancement is also presented. Here, the partnership would allow ASEAN to maintain its growing centrality in its many channels, one of which is its ASEAN way that guides the interactions and norm settings in the region. With all that laid out, it can be understood that the creation of the partnership does not make ASEAN lose its luster, rather it accentuates its centrality in the Indo-Pacific.